2017
DOI: 10.1016/j.jns.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

First reported cases of anti-NMDA receptor encephalitis in Vietnamese adolescents and adults

Abstract: IntroductionAnti-NMDA receptor encephalitis is increasingly recognised as an important differential diagnosis in patients with encephalitis of unknown aetiology. We report the first case series of patients diagnosed in Vietnam.MethodsSamples of CSF from patients with presumed encephalitis but negative microbiological investigations, who exhibited dyskinesia, autonomic instability or psychosis were tested for antibodies against the NR1 subunit of the glutamate (type-NMDA) receptor using an indirect immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Encephalomalacia was identified in 7 cases (more frequently in patients with a history of head trauma or stroke), and multifocal lesions were seen in 3 patients (multiple sclerosis, encephalomyelitis, cerebral metastasis). In 2017, Nguien Thi Hoang published a study with 9 patients with catatonia associated with anti-NMDA receptor encephalitis (Nguyen Thi Hoang et al, 2017). Among them, 3 had a normal brain CT, and 6 a brain MRI, of which one was abnormal showing bilateral hyperintensity in the image contrast within the medial temporal lobes.…”
Section: Structural Brain Mrimentioning
confidence: 99%
“…Encephalomalacia was identified in 7 cases (more frequently in patients with a history of head trauma or stroke), and multifocal lesions were seen in 3 patients (multiple sclerosis, encephalomyelitis, cerebral metastasis). In 2017, Nguien Thi Hoang published a study with 9 patients with catatonia associated with anti-NMDA receptor encephalitis (Nguyen Thi Hoang et al, 2017). Among them, 3 had a normal brain CT, and 6 a brain MRI, of which one was abnormal showing bilateral hyperintensity in the image contrast within the medial temporal lobes.…”
Section: Structural Brain Mrimentioning
confidence: 99%
“…A prospective study from the UK identified 20% of cases with an immune-mediated cause, including ADEM, NMDAR encephalitis and VGKC complex encephalitis 31 ; another from Thailand, found 24% of patients with encephalitis were associated with immune encephalitis 23 . A recent retrospective cohort study in the United States also identified 20% with an autoimmune cause 32 ; another from Vietnam found 9.1% had NMDAR encephalitis 33 . A systematic approach to autoantibody testing in the assessment of acute encephalitis patients may be required as early and accurate diagnosis of immune-mediated etiology is important for appropriate immunotherapy rather than empirical administration of antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient responded well to immunotherapy with methylprednisolone and IVIG. Although symptoms are usually severe, studies suggest that patients are usually highly responsive to therapy [ 9 ]. As per a reported case series of 99 patients with all-cause encephalitis, 9.1% were found to have anti-NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of these patients was 28 years, and 5 of 9 were females. Follow-up of these patients showed zero mortality and complete symptomatic recovery after treatment with high-dose corticosteroids and intravenous immunoglobulin [ 9 ]. Prompt diagnosis and early treatment will reduce mortality and ensure complete recovery.…”
Section: Discussionmentioning
confidence: 99%